Turning REST/NRSF Dysfunction in Huntington's Disease into a Pharmaceutical Target - Rigamonti, Dorotea; Mutti, Cesare; Zuccato, Chiara; Cattaneo, Elena; Contini, Alessandro (Current Pharmaceutical Design, 2009)
REST/NRSF is a transcription factor that represses transcription of several neuronal genes by binding to a DNA regulatory motif known as Repressor Element 1/Neuron-restrictive silencer element (RE1/NRSE). In Huntington's Disease, an inherited degenerative disease affecting the brain, REST/NRSF enters pathologically into the nucleus of affected cells, leading to the activation of the RE1/NRSE sites and causing decreased transcription of several important neuronal genes. Following this discovery, an effort has begun by some of the authors aimed at identifying compounds capable of antagonizing REST/NRSF silencing activity. Here we will review the underlying basis for focusing pharmaceutical efforts on REST/NRSF-RE1/NRSE system as well as some of the strategies for a rational drug design approach. We will highlight approaches aimed at identifying or designing small molecules able to impact REST/NRSF nuclear translocation, its DNA binding or, more generally, the formation of the REST/NRSF transcriptional complex, in the attempt to restore neuronal gene transcription in pathological conditions of the brain.
Keywords: computer aided drug design